A comparative analysis of the treatment of biodiversity impacts in mining Environmental Impact Assessments (EIAs) before and after 2013: experiences from the Mpumalanga province, South Africa - Pohlo, Reanetsie T. (University of the Free State, 2019)
Environmental Impact Assessment (EIA) is one of the environmental management tools employed by the relevant authorities to achieve the principles of sustainable development. Biodiversity Impact Assessment (BIA) studies are undertaken as part of the EIA process to ensure that the proposed development considers the potential impacts on the biodiversity. Studies on the state of South Africa’s biodiversity have revealed that biodiversity and ecosystems in the country are under serious threat; and mining is one of the major threats to the biodiversity. In 2013, the Mining and Biodiversity Guideline (DEA et al., 2013) was published, with the aim of improving the integration of biodiversity into the mining industry. This research analyses the treatment of biodiversity impacts in mining EIAs before and after the publication of this guideline. In order to achieve the aim of this research, a customised mining BIA report-review package was developed; and it was employed to review 46 mining BIA reports produced before and after 2013. Secondary data – by means of questionnaires were also employed to get an in-depth understanding of the treatment of biodiversity impacts in mining EIAs. The results of the study revealed that most BIAs failed to consider biodiversity issues properly in their assessments. For instance, the BIAs conducted before, and after 2013 received an overall satisfactory score of 43% and 57%, respectively. Areas of weakness include project description, sensitivity mapping, stakeholder consultation, consideration of alternatives, as well as monitoring. Faithful representation of the biodiversity specialist input to the main mining EIA report showed an improvement after 2013, by receiving an overall satisfactory score of 78%, compared to the 52% received before 2013. The results also revealed that the majority of the BIA reports complied with the minimum requirements for specialist studies stipulated by the National Environmental Management Act (Act No.107 0f 1998). The analysis of the questionnaires revealed several inadequacies and areas of weakness regarding the treatment of biodiversity impacts. These include poor consideration of indirect and cumulative impacts, failure to incorporate environmental thresholds, and the ecosystem approach – when assessing biodiversity impacts. A series of recommendations for improving the treatment of biodiversity impacts in mining EIAs was subsequently formulated. The development and implementation of sensitivity mapping guidelines, capacity building for biodiversity specialists and Environmental Assessment Practitioners (EAPs), and the application of the mitigation hierarchy, among others, is proposed to improve the consideration of biodiversity impacts in mining EIAs.
Dissertation (M.Sc. (Geography))--University of the Free State, 2019
Keywords: Environmental Impact Assessment (EIA); Biodiversity Impact Assessment (BIA); BIA report; Treatment of biodiversity; Mining EIAs; Mining and Biodiversity Guideline